The Parental Involvement and Learning Media in Health Education for Children with Autism Spectrum Disorder (ASD) - Yuliza, Wilda Tri; Yanti, Meyi (Journal of Health Sciences and Epidemiology, 2024)
Autism Spectrum Disorder (ASD) affects social communication and behavior, requiring specialized approaches for health education. Parental involvement and the type of learning media play a significant role in health education outcomes for children with ASD. This study examines the relationship between parental involvement, learning media (digital vs. traditional), and health education outcomes for children with ASD. A cross-sectional study was conducted with 83 parents of children diagnosed with ASD. Data were collected through structured questionnaires assessing parental involvement and the type of learning media used. Bivariate analysis was performed to examine associations between these variables. Most parents (78.3%) were female, and 55.4% used digital learning media. Children with high parental involvement had significantly higher self-care scores (mean = 7.6, p< 0.01) compared to those with lower involvement (mean = 6.3). Digital media was more effective than traditional media, with children using digital tools showing a 30% increase in health knowledge (p= 0.02). The combination of high parental involvement and digital media use produced the best educational outcomes (mean = 8.1, p = 0.001). High parental involvement and the use of digital learning media are positively associated with better health education outcomes in children with ASD. Interventions targeting increased parental engagement and enhanced access to digital learning media could improve health education for children with ASD.